2023
DOI: 10.3390/biomedicines11010124
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Protein B Plasma Levels: Reliability as a Biomarker in COPD Patients

Abstract: Background: The diagnosis of COPD is based on both clinical signs and functional tests. Although there are different functional tests used to assess COPD, no reliable biomarkers able to provide information on pathogenesis and severity are available. The aim of the present study is to explore the relationship between surfactant protein B (Sp-B) serum levels and clinical, radiological, and functional pulmonary parameters in COPD patients. Methods: Forty COPD patients and twenty smokers without airflow limitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…A recent study suggested that surfactant protein B was a lung-specific prognostic biomarker in COPD. 43 Dysregulation of surfactant proteins is associated with many eosinophilic lung diseases. 44 Future studies are needed to elucidate the role of surfactant proteins in eosinophilic exacerbation of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that surfactant protein B was a lung-specific prognostic biomarker in COPD. 43 Dysregulation of surfactant proteins is associated with many eosinophilic lung diseases. 44 Future studies are needed to elucidate the role of surfactant proteins in eosinophilic exacerbation of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 D'Ascanio et al showed that SpB might be considered as a useful marker in COPD assessment and provided prognostic information on lung functional decline. 17 Therefore, the present study aimed to assess whether GDF-15 and sST2 could be early indicators of AECOPD-PH. It has been reported that GDF-15 can be used as a signature in some diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous lung cancer risk prediction models including Bach [ 8 ], Spitz [ 9 ], the Liverpool Lung Project (LLP) and Liverpool Lung Project Incidence (LLPi) Risk Models [ 10 , 11 ], Hoggart [ 12 ], PLCOm2012 [ 13 ], Pittsburgh [ 7 ], and the Lung Cancer Risk Assessment Tool (LCRAT) [ 14 ] were developed to identify individuals at high risk of lung cancer and who may benefit from LCS [ 7 , 8 , 10 , 11 , 12 , 13 , 14 ]. Additional models such as the Lung Cancer Death Risk Assessment Tool (LCDRAT) [ 14 ] and the Kovalchik model [ 15 ] predict lung cancer mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Further improvements in lung cancer risk prediction may be achieved using biomarkers. Previously, our group established the merits of a four-marker protein panel (4MP) consisting of the precursor form of surfactant protein B (Pro-SFTPB) [ 8 , 9 , 10 ], cancer antigen 125 (CA125), carcinoembryonic antigen (CEA), and cytokeratin-19 fragment (CYFRA21-1). The Pro-SFTPB was found to result from the activation of the transcription factor NKX2.1, a known oncogene activated early during lung tumor development [ 10 ].…”
Section: Introductionmentioning
confidence: 99%